Formulation of Innovation Policy: Case of Bandung Smart City - Chaereyranba Sholeh; Sintaningrum Sintaningrum; Yogi Suprayogi Sugandi (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The aim of this study is to describe the policy innovation of the implementation of a smart city in Bandung. Heightening urban issues are becoming increasingly complex and limited resources are available to alleviate them, making the government to continue making policy innovations in order to improve the societal welfare. The smart city policy innovation implemented by the government of Bandung is expected to solve the priority problems of Bandung effectively and efficiently. In conducting a policy innovation, special attention should be paid to several important things such as regulation, community needs, and understanding the apparatus and those who contribute in the implementation of a smart city in Bandung. With the fulfillment of several policy innovation factors, the implementation of a smart city in Bandung can be successful and solve the problems that currently exist in the city. To analyze the smart city policy innovation in Bandung, the researchers used the policy innovation instrument phase from Susanna Borras and Charles Edquist. The method used in this research is a qualitative method with a descriptive analysis method, and data collection was carried out through literature and field study (observation, interview, and documentation). The result of this research is that the smart city policy innovation in Bandung has not been successfully implemented. This can be seen from the three instruments of policy innovation that have not been implemented in the implementation of a smart city in Bandung. The three instruments are a regulation instrument, an economic financial instrument, and a soft instrument.